Distributed Deformation in an Oceanic Transform System: Applying Statistical Tools to Structural and Paleomagnetic Data Near the Húsavík‐Flatey Fault, Northern Iceland. Issue 10 (27th October 2018) - Titus, Sarah J.; Chapman, William; Horst, Andrew J.; Brown, Maxwell; Davis, Joshua R.
Abstract: The right‐lateral Húsavík‐Flatey fault is part of the Tjörnes Fracture Zone, which links the offshore and onshore rift axes in northern Iceland. There has been debate about whether rocks near this fault have accommodated distributed off‐fault deformation, which is testable using paleomagnetic data. Recent studies from Flateyjarskagi show clockwise declination deflections that are largest near the fault. We augment these data with new structural and paleomagnetic measurements from 106 lava flows across three peninsulas—Flateyjarskagi, Tröllaskagi, and Tjörnes—also finding clockwise deflections that vary with distance from the fault. To test whether the deflections could be caused by off‐fault deformation, we combine our measurements with other regional data sets, applying several statistical tools including regressions of structural or paleomagnetic directions versus fault‐normal distance. To evaluate the significance and uncertainties of the regressions, we use permutation tests and bootstrapping. For Flateyjarskagi, our analysis suggests that lavas and dikes were deformed together; the regression results predict 4°–6° of rotation per kilometer about a steep, but not vertical, axis. Rocks on Tröllaskagi hint at similar spatial patterns with fault distance, but the data quality precludes a full analysis. Rocks on Tjörnes show no spatial patterns, but they preserve a temporal history, where rotation seems to have ceased after deposition of the Pliocene‐age Tjörnes beds. Using constraints from our statistical analyses, geochronology, and comparisons with the transform system in southern Iceland, we propose several modifications to models for the evolution of axial rift zones in northern Iceland. Key Points: Paleomagnetic data show clockwise rotation of rocks near the Húsavík‐Flatey fault We use statistical tools such as regressions to analyze patterns of off‐fault deformation in directional data We propose a model for the tectonic evolution in north Iceland that incorporates our statistically derived results